The significance of the monastic training system and the essential factors for the spiritual development of bhikkhunīs as depicted in early Buddhist discourses - Sri Utami; Nguyen Thi My Loc (SMARATUNGGA: JURNAL OF EDUCATION AND BUDDHIST STUDIES, 2022)
The Buddha presents and establishes a new approach toward women's education by accepting Mahāpajāpatī Gotamī to enter the life of a saṅgha and lead a life based on the Dhamma and Vinaya as a bhikkhunī. This was a great event in the history of the emergence of monastic training for women. The study investigates the essential factors supporting the development of bhikkhunī monastic life in the past based on early Buddhist discourses. Paper analysis methods were used in this study, and the documents used by the researchers were research material from the Sutta Piṭaka and Vinaya Piṭaka. The data was analyzed using descriptive qualitative analysis. The results revealed that by fulfilling the essential factors of the bhikkhunī monastic training, the Noble Ladies who had developed their lives in the Dhamma and Vinaya in historical times successfully achieved the liberation of saṃsara. The results of this study contribute to providing several facts that women can reach the highest spiritual achievement as achieved by men.